A preliminary study using the Energy Dispersive X-Rays (EDX) technique on the electroless plated ceramic body / Saidatulakmar Shamsuddin ... [et al.] - Shamsuddin, Saidatulakmar; Wanik, Baharuddin; Mohd Noor, Ahmad Fauzi; Ahmad, Zainal Ariffin (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2004)
The study of this research is focused on finding the optimum parameter of electroless plating. It is shown by the quality of the nickel coating. From this study, it is found that the best quality of coating is produced at the electroless plating parameter of 80°C and for the duration of soaking between 15-30 minutes However a few days after the electroless plating process has been done, it is found that the layer of electroless nickel plating is lost if the electroplating process is not done immediately after the electroless plating process. To investigate the loss of the nickel coating after the electroless plating process, the energy dispersive x-rays (EDX) technique is used. Results show that the nickel has penetrated into the ceramic through the capillary action, due to porosity. Therefore we suggest that the electroplating process should be done immediately after the electroless plating process. Basically, this research has proved that the clay ceramic body can be coated by nickel.